The development and standardization of a picture SRT test for adults and children in Kannada - Rajashekar (Journal of All India Institute of Speech and Hearing)
Speech audiometry embraces the clinical procedures used in measuring the auditory response to speech stimuli. Speech Reception Threshold (or threshold of intelligibility) and speech sound discrimination are the stimulus dimensions assessed most frequently in clinical practice. Speech reception threshold is usually defined as the "lowest hearing level at which a person repeats correctly 50 percent of the spondaic words heard by him ".